The incidence of inflow and drain pain and associated risk factors for patients on peritoneal dialysis - Shun Hua; Peiyi Cao; Guanji Zhang; Guanglan Li; Simin Jiang; Yiping Xu; Jianbo Li; Jianwen Yu; Naya Huang; Jianxiong Lin; Xiao Yang; Wei Chen; et al. (BMC Nephrology)
Abstract Background The high prevalence and prolonged duration of inflow pain and drain pain experienced by peritoneal dialysis (PD) patients following PD catheter implantation impact their quality of life. However, there is limited data on the frequency and predisposing factors of these pains in the Chinese population undergoing peritoneal dialysis. Methods This study encompassed individuals who underwent peritoneal dialysis catheter implantation at our institution from September 1, 2023, to March 31, 2024. Patients’ experiences of inflow pain and drain pain were evaluated using a questionnaire survey and the visual analog scale (VAS), with pain status followed up via telephone for 3 months post-surgery. Results A total of 141 patients were included in this study. Inflow pain occurred at rates of 56.0%, 20.9%, 16.9%, and 17.3% at 1-week, 1-month, 2-month, and 3-month postoperatively, respectively, while drain pain rates were 51.8%, 24.3%, 22.3%, and 19.5% for the same period. Slowing down the infusion rate of dialysate (57.0%) or stopping its drainage (60.3%) proved effective in reducing pain. Logistic regression analysis revealed that age (OR = 0.96, P = 0.02), gender (OR = 0.37, P = 0.03), and the method of PD catheter implantation (OR = 2.37, P = 0.04) were independent factors associated with inflow or drain pain within 1-week postoperatively. Conclusion The occurrence of inflow pain and drain pain following peritoneal dialysis catheter implantation is notable. Age, gender, and the method of catheter implantation were identified as independent factors influencing the incidence of inflow or drain pain within the first postoperative week.